Ichthyofaunal survey of the Riacho Goulart, tributary of the Tiete River (upper Parana basin). - Pazian, Marlon F.; Leal, Hugo Muelas Moura; Lalucce, Marcio (My University, 2011)
Fishes assessed in the present study were collected in the Riacho Goulart, a small tributary of Tiete River, upper Parana basin. In order to sample different habitats, four collection sites were selected. A total of 1,241 individuals belonging to 30 species, 15 families, and six orders were captured. The list of fish species presented herein is important for the knowledge of the biodiversity of low Tiete basin.